Case Report : Rehabilitation Intervention in Improving Infant’s Oromotor Skill and Body Weight - Merliana Sari Situmeang; Ida Ayu Diana J.S (Medica Hospitalia : Journal of Clinical Medicine, 2024)
Introduction Preterm birth rates are still very high. Global data found that preterm babies occurred in 11% of all live births. A recent study showed that more than 25% of neonates baby born between 28 and 32 weeks of gestation, developed disorders condition at the age of two, and this ratio reached 40% at the age of ten. Preterm infants had higher risk of poor motoric skills, such as subtle deficits in eye-hand coordination, sensory-motor integration, manual dexterity, and gross motor skills that lead to poor feeding skills and neuromotor development delay. Therefore, interventions need to be done to optimize growth and development. Case A 10-day-old male infant consulted by the Medical Rehabilitation department due to feeding difficulty and low birth weight. At 10 days old, the patient weighs 1550 grams, length 44 cm, head circumference 31 cm, and the non-nutritive scoring (NNS) was 45. The patient was given proper positioning, oral motor stimulation (OMS) with the Fucile method for 1 week in the hospital and the treatment continue at home. After 2 weeks of intervention, the infant’s body weight increased to 2010 grams, body length 45 cm, head circumference 32 cm, and the non-nutritive scoring (NNS) became 86. Conclusion Oral motor stimulation improves oral motor skills such as sucking and swallowing reflexes in infants without organ abnormalities thus optimized good oral feeding ability and weight gain acceleration.